Detection and Quantification of Fluorescent Cell Clusters in Cryo-Imaging. (18th March 2012) - Steyer, Grant J.; Dong, Feng; Kanodia, Lehar; Roy, Debashish; Penn, Marc; Wilson, David L.
Abstract : We developed and evaluated an algorithm for enumerating fluorescently labeled cells (e.g., stem and cancer cells) in mouse-sized, microscopic-resolution, cryo-image volumes. Fluorescent cell clusters were detected, segmented, and then fit with a model which incorporated a priori information about cell size, shape, and intensity. The robust algorithm performed well in phantom and tissue imaging tests, including accurate (<2% error) counting of cells in mouse. Preliminary experiments demonstrate that cryo-imaging and software can uniquely analyze delivery, homing to an organ and tissue distribution of stem cell therapeutics.